2021
DOI: 10.1016/j.bbrep.2021.101108
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of UBE2V1 in cervical cancer

Abstract: The majority of cervical cancer (CC) patients are caused by the high-risk human papillomavirus (HPV) infection Although they are preventable and controllable, the mortality rate is still high. It is essential to identify the biomarkers for early screening and diagnosis of CC to improve the prognosis of patients with CC. The conjugating enzyme 2 (E2) family members are the key components of ubiquitin protease system. However, the role of E2 family in CC remains unclear. We aimed to investigate the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…UBE2V1 plays an important role in protein aggregate formation, study indicated that inhibition of UBE2V1 may provide a novel therapeutic target to treat cardiac proteinopathies [ 37 ]. In addition, UBE2V1 of aqueous humor expressed in the patients with Retinoblastoma (RB) [ 38 ], similarly, high expression of UBE2V1 was correlated to the poor prognosis of patients with cervical cancer [ 39 ]. The role of UBE2V1 in skin disease is unfamiliar, accordingly, UBE2V1 enables cellular responses toward fibroblast growth factor signaling in endothelium, acts as a key modulator for angiogenesis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…UBE2V1 plays an important role in protein aggregate formation, study indicated that inhibition of UBE2V1 may provide a novel therapeutic target to treat cardiac proteinopathies [ 37 ]. In addition, UBE2V1 of aqueous humor expressed in the patients with Retinoblastoma (RB) [ 38 ], similarly, high expression of UBE2V1 was correlated to the poor prognosis of patients with cervical cancer [ 39 ]. The role of UBE2V1 in skin disease is unfamiliar, accordingly, UBE2V1 enables cellular responses toward fibroblast growth factor signaling in endothelium, acts as a key modulator for angiogenesis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitin-conjugating enzyme E2 variant 1 (Ube2v1), also known as Uev1a, is a mammalian homolog of yeast MMS2 and an auxiliary factor of the ubiquitin-conjugating enzyme, Ube2n (10). Ube2v1 is a unique sub-member of the E2 family as it lacks the conserved catalytic cysteine in E2 (11). Ube2v1 complexes with Ube2n and activates the nuclear factor κB (NF-κB) signaling pathway, which is involved in the regulation of cancer (12).…”
Section: Introductionmentioning
confidence: 99%